حقوق المتحولين جنسيا في ماليزيا : دراسة فقهية تحليلية مقاصدية - Farhan Hasmady (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
Transgenders are a marginalized group in many parts of the world including Malaysia. For this reason, some segments of society have demanded rights in favor of the transgenders. The aim of this research is to study the correct legal Fiqhi position towards sex reassignment, and to study the rights of transgender people in Malaysia from the perspective of Maqasid Syariah. The researcher has followed a set of methodologies with which he addressed the topic at hand. Through the inductive methodology the researcher compiled and discussed the positions of Muslim jurists with regards to sex reassignment and the references of each position. The researcher came to a conclusion and provided justifications for his choice. The researcher also gave an overview of efforts exerted in demanding rights for transgenders around the world. Then an overview was also presented on the transgender community in Malaysia and rights demanded were also highlighted. Through the analytical approach, the researcher discussed the issue of transgenders' rights and its legitimacy in light of Maqasid Syariah. A field study was also conducted through correspondence and interviews with transgenders, as well as with activists and volunteers. The study concluded that the impermissibility of sex reassignment for transgenders as they are not suffering from physical defects. The study also found the importance of observing the general rights that should be given to all without excluding the transgender community. As for the demanded rights, they are subject to the view of Shariah in terms of being a means to achieve objectives and goals the Shariah aims for.